1989
DOI: 10.1002/bit.260341106
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized enzyme cellulose hollow fibers: III. Physical properties and in vitro biocompatibility

Abstract: The initial testing of the safety of a cellulose-heparinase hollow fiber device was assessed with respect to physical properties and in vitro biocompatibility. The material cleared urea and creatinine without passing albumin, even at high flow rates. The clearance of urea and creatinine by cellulose-heparinase was equal or slightly reduced in comparision to the cellulose device. The cellulose-neparinase device tolerance to now rates was also unchanged. In addition, scanning electron microscopy of the lumen est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…Earlier studies suggested the importance of basic residues in heparinase I activity (Comfort et al, 1989;Leckband and Langer, 1991). Recently, we found that cysteine 135 of heparinase I is catalytically active .…”
mentioning
confidence: 76%
“…Earlier studies suggested the importance of basic residues in heparinase I activity (Comfort et al, 1989;Leckband and Langer, 1991). Recently, we found that cysteine 135 of heparinase I is catalytically active .…”
mentioning
confidence: 76%
“…The effects of sulfhydryl modifications demonstrated that cysteine-reactive probes resulted in loss of enzymatic activity and the presence of a free cysteine (Leckband & Langer, 1991). In addition, earlier biochemical studies reported that heparinase I contained three to four cysteines (Yang et al, 1985) and a disulfide bond (Comfort et al, 1989). Taking all the above results together we set to address the number, the states, and the role of cysteines in heparinase I.…”
mentioning
confidence: 96%
“…Heparinase I is believed to bind heparin through the lysine residues on the enzyme surface (Yang et al, 1985;Linhardt et al, 1982Linhardt et al, , 1990). The observation that modification by amine-reactive reagents and immobilization of heparinase I on amine-reactive supports result in extensive activity losses suggested the importance of lysines (Bernstein et al, 1988;Comfort et al, 1989;Leckband & Langer, 1991). In addition, evidence for an electrostatic nature of the interaction lies in the pH and ionic strength dependence of heparinase I activity (Yang et al, 1985).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By the end of the 1980s, heparinase was immobilized within cellulosic hollow fibres to remove heparin's anticoagulant activity in blood filters [33][34][35]. Our fibres were endowed by simple capillary forces with two biotherapeutic model drugs that were not immobilized, but subsequently freeze-dried: The debriding enzyme Krillase ® , a protease of the antarctic krill (Euphasia superba) and antibiotic bacteriophages.…”
Section: Discussionmentioning
confidence: 99%